Perlindungan Hukum terhadap Nasabah dalam Sistem Mobile Banking - Wandya Putri Cahyani (CV Rewang Rencang, 2025)
Various banking products that should be developed show that banks must be able to track and use technology as part of their service delivery system. Mobile banking allows users to open account balance information or transfer money using their mobile phones. One of the problems with mobile banking is transaction errors, repeated transactions due to delayed text messages, and the large amount of data transfer that should occur via the internet so that data lags. Data delays occur at certain times because there are two servers, namely the bank server and the cellular operator server. That way if one of the servers experiences problems, it will disrupt the transaction process.